Online teaching and learning effectiveness for kindergartens, primary and secondary schools - Hong Sheung Chui; Wai Tin Hui; Samuel Wing Ho Chui (Cogent Education)
Online teaching was adopted in Hong Kong and many other places around the world due to lockdown policies during the COVID-19 pandemic. This research explores the online teaching and learning effectiveness of Kindergarten, Primary and Secondary students in Hong Kong as perceived by teachers. Factors including students’ family support, school support, teachers’ technology competence, and perceived teaching and learning effectiveness were measured by a questionnaire. 427 teachers from kindergartens, primary schools and secondary schools completed the questionnaire in 2023. Analysis by Confirmatory Factor Analysis supports the reliability and discriminant validity of the questionnaire. Structural Equation Modeling was used to test the hypotheses. The findings show that family support, school support and teaching effectiveness positively affect students’ online learning effectiveness. Teaching effectiveness is associated with school support and teachers’ technology competence in online teaching preparation. The relationships among various variables are the same for kindergartens, primary schools to secondary schools. It can cast light on strategies to improve online teaching and learning effectiveness for kindergartens, primary and secondary schools.